2018
DOI: 10.1590/1414-431x20187665
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus polysaccharides decrease proliferation, migration, and invasion but increase apoptosis of human osteosarcoma cells by up-regulation of microRNA-133a

Abstract: Osteosarcoma (OS) has a high incidence, malignity, and frequency of recurrence and metastasis. In this study, we aimed to explore the potential anti-cancer effects of Astragalus polysaccharides (APS) on human OS MG63 cells as well as underlying mechanisms. Viability of MG63 cells was assessed by CCK-8 assay to determine the adequate concentration of APS. Then, effects of APS on MG63 cell proliferation, cell cycle distribution, apoptosis, and migration and invasion were analyzed by BrdU incorporation, PI staini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 42 publications
1
17
1
Order By: Relevance
“…Specifically, we demonstrate here that WIN markedly reduced the migratory ability of osteosarcoma MG63 cells, and this effect was accompanied by a dramatic reduction in the extracellular activity and intracellular levels of MMP2 and MMP9 metalloproteases. Although conflicting data are present in the literature regarding the expression levels of metalloproteases in osteosarcoma cells [31,32], we found that, in our serum-free conditions, both the intracellular levels and extracellular activity of MMP9 were higher than those of MMP2. Fragmentary data in the literature demonstrate that WIN can inhibit the epithelial mesenchymal transition and migration in different cancer cell models [33,34] In an attempt to clarify the mechanism of the anti-migratory effect of WIN in osteosarcoma cells, our study specifically focuses on a possible involvement of the matricellular protein SPARC and a hypothetical role exerted by miR-29b1.…”
Section: Discussioncontrasting
confidence: 68%
“…Specifically, we demonstrate here that WIN markedly reduced the migratory ability of osteosarcoma MG63 cells, and this effect was accompanied by a dramatic reduction in the extracellular activity and intracellular levels of MMP2 and MMP9 metalloproteases. Although conflicting data are present in the literature regarding the expression levels of metalloproteases in osteosarcoma cells [31,32], we found that, in our serum-free conditions, both the intracellular levels and extracellular activity of MMP9 were higher than those of MMP2. Fragmentary data in the literature demonstrate that WIN can inhibit the epithelial mesenchymal transition and migration in different cancer cell models [33,34] In an attempt to clarify the mechanism of the anti-migratory effect of WIN in osteosarcoma cells, our study specifically focuses on a possible involvement of the matricellular protein SPARC and a hypothetical role exerted by miR-29b1.…”
Section: Discussioncontrasting
confidence: 68%
“…Several studies have reported that APS exhibits its growth inhibitory effects on cancer cells through modulation of miRNAs [6,15]. Based on the studies reported above, we postulated that APS induced antiproliferative and pro-apoptotic effects in OC through regulation of miRNAs.…”
Section: Aps Down-regulated the Expression Of Mir-27a In Oc Cellsmentioning
confidence: 69%
“…Resveratrol could alter the expressions of many miRNAs in PC-3M-MM2 cells, which may contribute to its anti-tumor property in prostate cancer [23]. A recent study has demonstrated that APS play a tumor suppressive role in human osteosarcoma cells by up-regulation of miR-133a [6]. It is for that reason that we investigated the role of miRNA in the anti-tumor property of APS.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It was demonstrated that APS could induce the apoptosis of human HCC cells by decreasing the expression of Notch1 [144] (Figure 4⑩). What is more, APS was also proved to repress proliferation, migration and invasion while induced apoptosis of human osteosarcoma MG63 cells by up-regulating miR-133a and then inactivating JNK pathway [145].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%